Extracellular Vesicles Mediate Immune Responses to Tissue-Associated Self-Antigens: Role in Solid Organ Transplantations - Ravichandran, Ranjithkumar; Bansal, Sandhya; Rahman, Mohammad; Sureshbabu, Angara; Sankpal, Narendra; Fleming, Timothy; Bharat, Ankit; Mohanakumar, Thalachallour (Frontiers in Immunology, 2022)
Transplantation is a treatment option for patients diagnosed with end-stage organ diseases; however, long-term graft survival is affected by rejection of the transplanted organ by immune and nonimmune responses. Several studies have demonstrated that both acute and chronic rejection can occur after transplantation of kidney, heart, and lungs. A strong correlation has been reported between de novo synthesis of donor-specific antibodies (HLA-DSAs) and development of both acute and chronic rejection; however, some transplant recipients with chronic rejection do not have detectable HLA-DSAs. Studies of sera from such patients demonstrate that immune responses to tissue-associated antigens (TaAgs) may also play an important role in the development of chronic rejection, either alone or in combination with HLA-DSAs. The synergistic effect between HLA-DSAs and antibodies to TaAgs is being established, but the underlying mechanism is yet to be defined. We hypothesize that HLA-DSAs damage the transplanted donor organ resulting in stress and leading to the release of extracellular vesicles, which contribute to chronic rejection. These vesicles express both donor human leukocyte antigen (HLA) and non-HLA TaAgs, which can activate antigen-presenting cells and lead to immune responses and development of antibodies to both donor HLA and non-HLA tissue-associated Ags. Extracellular vesicles are released by cells under many circumstances due to both physiological and pathological conditions. Primarily employing clinical specimens obtained from human lung transplant recipients undergoing acute or chronic rejection, our group has demonstrated that circulating extracellular vesicles display both mismatched donor HLA molecules and lung-associated Ags (collagen-V and K-alpha 1 tubulin). This review focuses on recent studies demonstrating an important role of antibodies to tissue-associated Ags in the rejection of transplanted organs, particularly chronic rejection. We will also discuss the important role of extracellular vesicles released from transplanted organs in cross-talk between alloimmunity and autoimmunity to tissue-associated Ags after solid organ transplantation.